28 nm FDSOI analog and RF Figures of Merit at N2 cryogenic temperatures. (September 2019) - Kazemi Esfeh, B.; Planes, N.; Haond, M.; Raskin, J.-P.; Flandre, D.; Kilchytska, V.
Abstract: This work presents a detailed characterization of 28 nm FDSOI CMOS process at cryogenic temperatures. Electrostatic, Analog and RF Figures of Merit (FoM) are studied. At liquid nitrogen temperatures, 30% to 200% enhancement of drain current, Id, and maximum transconductance, gm_max, values are demonstrated. Current gain cutoff frequency, fT, increase by about 85 GHz is shown. Temperature behavior of analog and RF FoMs is discussed in terms of mobility and series resistance effect. This study suggests 28 nm FDSOI as a good contender for future read-out electronics operated at cryogenic temperatures (as e.g. around qubits or in space).